Azotobacter bryophylli sp. nov., isolated from the succulent plant Bryophyllum pinnatum. Issue 7 (2nd May 2019) - Liu, Lihui; Yuan, Tao; An, Qianli; Yang, Meiyan; Mao, Xiaoyun; Mo, Cehui; Tan, Zhiyuan; Peng, Guixiang
Abstract : A Gram-stain-negative, aerobic, nitrogen-fixing bacterium, designated strain L461 T, was isolated from leaves of Bryophyllum pinnatum growing at the South China Agricultural University. Phylogenetic analysis of the 16S rRNA gene sequence indicated it as a member of the genus Azotobacter closely related to Azotobacter beijerinckii JCM 20725 T (97.82 % similarity) and Azotobacter chroococcum ATCC 9043 T (97.34 %). Its major fatty acid components were C16 : 1 ω9 c and C16 : 0 . Its predominant isoprenoid quinone was Q-9. Its major polar lipids were phosphatidylethanolamine, phosphatidylglycerol, aminophospholipid, phospholipid and one unknown lipid. Its DNA G+C content was 64.9 mol% (Tm). DNA–DNA relatedness values between strain L461 T and the reference strains of A. beijerinckii and A. chroococcum were 46.43 and 28.23 %, respectively. Biological and biochemical tests, protein patterns, genomic DNA fingerprinting, and comparison of cellular fatty acids distinguished strain L461 T from the closely related Azotobacter species. Based on these data, the novel species Azotobacter bryophylli sp. nov. is proposed, with the type strain L461 T (=KCTC 62195 T =GDMCC 1.1250 T ).